Host-microbe interactions in the gut of Drosophila melanogaster - Kuraishi, Takayuki; Hori, Aki; Kurata, Shoichiro (Frontiers in Physiology, 2013)
Many insect species subsist on decaying and contaminated matter and are thus exposed to large quantities of microorganisms. To control beneficial commensals and combat infectious pathogens, insects must be armed with efficient systems for microbial recognition, signaling pathways, and effector molecules. The molecular mechanisms regulating these host-microbe interactions in insects have been largely clarified in Drosophila melanogaster with its powerful genetic and genomic tools. Here we review recent advances in this field, focusing mainly on the relationships between microbes and epithelial cells in the intestinal tract where the host exposure to the external environment is most frequent.